How do online shopping platforms shape compulsive buying? A case study of university student - Nita Luciana; R.A Febrianti (International Journal of Research and Applied Technology (INJURATECH), 2022)
The purpose of this study is to understand the antecedents of consumer compulsive buying behavior. This study is carried out using the variable of hedonistic shopping experience, emotional shopping behavior, and heavy social networking to predict compulsive buying. This study is carried out using quantitative approach in 125 students of Widyatama University. The data is collected using survey method by distributing questionnaires through online platforms to the respondents. The data is then processed using regression method with SPSS 25 software. The results of this study indicate that hedonistic shopping experience, emotional shopping behavior, and heavy social networking has a positive and significant influence on consumer compulsive buying.